Microbiologic, Agrochemical and Allelopathic Soil Status Under Lavandula L. Plants Species in Forest-Steppe Zone - Yunosheva, Olena Petrivna; Ellanska, Natalia (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The article reports the results of microbiological, agrochemical and allelopathic studies of the influence of Lavandula angustifolia Mill. and Lavandula hybrida Rev. introductive plants on the soil status. The aim of this study was to analyze the effect of hydrothermal and soil conditions of Forest-Steppe zone on the microbial cenosis formation and dynamics of taxonomic and ecology-trophic groups of microorganisms, the soil allelopathic activity and the ratio of biogenic elements. The analysis of the functional structure of microbial cenosis in the rhizosphere of lavender and lavandin shows a decreased quantity of micromicetes and an increase in the amount of spore-forming bacteria. The allelopathic activity of soil under lavender is characterized by a low level of toxicity. The processes of mineralization of organic matter in the soil were quite balanced. The influence of allelochemicals on the distribution of macro and microelements in the soil during lavender cultivation has been studied. The obtained results prove the positive effect of the studied plants on the microbiocenose and physical-chemical soil state that should be taken into account for their gardening.